Hydrophobic bio-binders for cathode formulations
By using a double emulsion of hydrogel biosource polymer and biosource hydrophobic wax in the cathode of a biofuel cell, the problems of water flooding and uneven oxygen diffusion are solved, and the adjustable hydrophobicity and biodegradability of the cathode are achieved, thereby improving the battery performance and life.
Patent Information
- Application Number
- CN202380052936.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-11
- Filing Date
- 2023-07-10
- Publication Date
- 2025-03-04
AI Technical Summary
There are problems of water flooding and uneven oxygen diffusion in biofuel cells, resulting in reduced battery performance and shortened lifetime, and the lack of degradable and biologically derived hydrophobic enhancers in the prior art.
A double emulsion composed of hydrogel biosource polymer and biosource hydrophobic wax is used as a hydrophobic composition and is added to the bioactive ink for the preparation of cathode ink preparation for bioenzyme fuel cells.
The adjustable hydrophobicity of the cathode is achieved, the oxygen concentration near the catalytic center is improved, the good proton conductivity is maintained, the effective life of the enzyme is extended, and the entire system is maintained with biodegradability.
Smart Images

Figure CN119563248A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the manufacture of hydrophobic double emulsions (also referred to as "hydrophobic biobinders") to be integrated into biocathode inks in order to provide cathode ink formulations for hydrophobic biocathodes, enhance oxygen diffusion, avoid flooding without the use of fluorinated polymers, and keep the overall biofuel cell containing the hydrophobic double emulsion biodegradable.
[0002] In the following description, references in square brackets ([ ]) refer to the reference list at the end of the text. Background Art
[0003] Biofuel cells offer an attractive way to provide environmentally friendly and sustainable electricity to electronic devices, particularly small portable devices for applications such as healthcare, environmental monitoring, and biodefense. Given that enzyme-based fuel cells can operate using abundant substrates (i.e., glucose and oxygen) found in biofluids and environmental effluents, while exhibiting power densities that are generally superior to those of microbial fuel cells, they offer an attractive proposition for augmenting or self-powering small wearable or implantable devices [1,2,3]. Furthermore, paper-based devices are increasingly being proposed for these types of applications, as their light weight, small form factor, and flexibility allow them to be conformed to a range of different surfaces.
[0004] One of the key issues associated with fuel cells is water management, which requires a delicate water balance scheme between system hydration and cathode flooding.
[0005] On the one hand, water is necessary for the membrane to promote proton conductivity. On the other hand, if excessive water fills the pores of the catalyst layer (CL) and gas diffusion layer (GDL), the electrode reactions will become mass transfer limited, resulting in a rapid drop in cell voltage and immediate degradation of cell performance. Given the fact that water is generated by the oxygen reduction reaction within the CL and transported from the anode to the cathode by electroosmotic drag, proper water flooding prevention in cathode design and operation is critical to ensure high performance and extended lifetime of the fuel cell.
[0006] During operation, the properties of the CL and GDL significantly affect the water balance in the fuel cell. Sinha et al. [4] studied the profound effects of the underlying structure and surface wettability on pore-level liquid water transport and interfacial dynamics in the GDL of a fuel cell.
[0007] Although the importance of GDL in preventing flooding has been extensively studied, the role of water balance in Clin fuel cells has never been studied in depth either experimentally or numerically. The CL can act as a watershed in a fuel cell to regulate the balance between liquid water and vapor. Park et al. [5] numerically showed that different wettability in the CL and GDL can significantly affect the liquid water flow pattern and thus the performance of the cell.
[0008] Different strategies have been reported in the literature to modify the structure of the cathode to improve the performance of the entire battery stack.
[0009] Qiu et al. [6] developed a novel cathode structure with a dual CL that contains a hydrophilic inner layer covered with a hydrophobic layer. Their MEA using this dual CL improved Pt utilization, reduced the interfacial resistance between the CL and the GDL, and enhanced mass transfer, resulting in a higher performance MEA. Wei et al. [7] designed a cathode structure with gradient Pt nanowires that improved Pt utilization and promoted mass transfer, resulting in high performance. Deshmukh et al. [8] prepared an MEA with a micropatterned electrode structure that improved performance by alleviating cathode flooding and facilitating reactant diffusion. The above studies focus on the structural design of the CL to improve MEA performance. Another way to improve MEA performance and water management is to adjust the hydrophilicity and hydrophobicity of the CL or GDL [9]. Oh et al.
[10] introduced poly(vinylidene fluoride-co-hexafluoropropylene) (P(VdF-co-HFP)) copolymer as a binder in the CL to increase its hydrophobicity and prevent flooding. Li et al.
[11] improved oxygen diffusion and water management by adding dimethyl silicone oil to CL to increase oxygen permeability and hydrophobicity, thereby enhancing MEA performance. Hiramitsu et al.
[12] designed a GDL with a smaller pore structure, which made the CL more resistant to water flooding. In previous work, Chi et al.
[13] improved water management by adding polytetrafluoroethylene (PTFE) to CL to balance hydrophobicity and hydrophilicity.
[0010] In the case of biofuel cells, water management and oxygen mass transfer are also essential to ensure optimal performance and extended lifetime. Controlled hydrophobicity of the cathode can be achieved by adding a hydrophobic binder emulsion to its composition.
[0011] In addition, bio-enzyme fuel cells have the potential to be biodegradable and bio-based due to the use of bio-based catalysts. From an application point of view, this environmental parameter is particularly important and limits the formulation of materials used in their compositions. Currently, the field of biofuel cells has not used biodegradable or bio-derived materials as hydrophobic enhancers.
[0012] Currently, the development of global agriculture and issues related to food security have raised many issues, including the need to improve the preservation of agricultural products after harvest, especially fresh fruits and vegetables. Therefore, many studies have been conducted on various food preservation methods to ensure quality during transportation. Some studies aim to make protective films that are environmentally friendly and safe for consumers, increase value by using local raw materials, and promote the export potential of fresh fruits and vegetables.
[0013] Various natural polymer materials, including polysaccharides (chitosan, cellulose, starch, and their derivatives), proteins (gelatin and soy protein), and lipids (beeswax, candelilla wax, and carnauba wax), have been used to develop edible emulsion-based coatings instead of single or synthetic polymers [14,15]. Chitosan is a natural polycationic polysaccharide that is widely used as a coating material due to its excellent film-forming ability and antimicrobial activity [16,17], but its poor flexibility and ductility greatly limit its application. As an amphoteric derivative of chitosan, carboxymethyl chitosan (CCS) has improved water solubility and retains other properties of chitosan, and it has been widely used in food packaging [18-20]. However, most coating materials derived from water-soluble polymers show high hydrophilicity, which greatly limits their application in humid environments. Lipid compounds, such as wax materials (beeswax, candelilla wax, and carnauba wax), have high water-blocking ability; unfortunately, the coating films formed from pure waxes have poor mechanical strength. Polysaccharides (such as cellulose and its derivatives) can be used to mix with wax components to form films with reduced water vapor permeability and water swelling [21, 22]. Therefore, it is of great significance to prepare edible coatings composed of CCS, cellulose and beeswax by Pickering emulsion method to overcome the shortcomings of coatings made of single components.
[0014] In biofuel cells, catalysis is based on enzymatic reactions. The immobilization of enzymes in the presence or absence of redox mediators provides many advantages, such as improved electron transfer and long-term stability. However, immobilization can also affect the stability and / or activity of the enzyme. The stability of the immobilized enzyme depends on the nature and strength of electrode binding, the immobilization conditions, the degree of restriction, and the conditions under which the enzymatic reaction occurs in the electrode during operation. Each immobilization method has its advantages and disadvantages. Therefore, the immobilization process must be carefully selected to avoid enzyme denaturation and loss of the structural freedom required for its activity.
[0015] The main immobilization techniques are physical adsorption, reconstitution of apoenzymes, encapsulation, covalent grafting, immobilization by cross-linking, and immobilization in hydrogels.
[0016] One strategy for enzyme immobilization and stabilization is to use micellar polymers. Enzymes in solution are typically active for a few hours to a few days. By encapsulating them in a hydrogel and binding them to an electrode surface, this lifetime can be extended to 7 to 20 days. However, researchers at Saint Louis University have extended the lifetime of active enzymes on electrode surfaces to more than a year by immobilizing them within hydrophobically modified micellar polymers
[23] .
[0017] Micellar polymers such as Nafion TM Hydrophobic modification of Nafion (and chitosan) is used to tailor the micellar pore or pocket structure to an optimal size for enzyme immobilization while also ensuring a hydrophobic and pH-buffered microenvironment for optimal enzyme activity. This strategy on chitosan has been shown to not only extend the effective lifetime of the enzyme but also increase the enzymatic activity of the enzyme by up to 2.5-fold
[24] . TM Membranes can also be used as separators between electrodes to ensure a hydrophobic environment at the cathode
[25] . However, fluoropolymers are not a sustainable solution, for example due to their extremely strong persistence or the emissions associated with their production, use and disposal
[26] . Moreover, such hydrophobic modifications involve expensive and lengthy freeze-drying processes to produce the polymers. In addition, such hydrophobic modifications render the polymers completely hydrophobic and do not allow this property to be adjusted in a controlled manner.
[0018] Therefore, there remains a need to provide a biodegradable hydrophobic composition for a biofuel cell cathode which does not have the prior art disadvantages of the prior art. Summary of the invention
[0019] Thus, the inventors have solved the dual challenges of flooding the cathode and fine-tuning the hydrophobic / hydrophilic ratio of the cathode layer by using bio-based products, while maintaining the overall biodegradability of the fuel cell.
[0020] To this end, the inventors have realized a double emulsion made of a hydrogel bio-source polymer (such as, for example, chitosan) as the first emulsion and a bio-source hydrophobic wax (such as, for example, beeswax) as the second emulsion. This double emulsion formulation is then added to the composition of a bioactive ink as the main binder for the biocathode of a bio-enzymatic fuel cell.
[0021] Thus, the present inventors have provided a biodegradable hydrophobic composition for a biofuel cell cathode having a tunable hydrophilicity / hydrophobicity ratio.
[0022] Therefore, one object of the present invention is a cathode ink formulation comprising a mixture of a hydrogel bio-derived polymer as a first emulsion and a bio-derived hydrophobic wax as a second emulsion and a bioactive ink.
[0023] By "hydrogel" bioderived polymer is meant a three-dimensional network of hydrophilic polymers that swells and retains liquid when in water.
[0024] By "biosourced" is meant a product or material that is made entirely or substantially from materials of natural origin (ie, plant or animal origin) and is sustainable.
[0025] By polymer, we mean a macromolecule composed of repeating subunits, monomers. For the purposes of this invention, this definition does not include fluorinated polymers, as they are not sustainable materials.
[0026] The so-called "ink" refers to a fluid or viscous substance used for printing, which is composed of at least a pigment and a binder.
[0027] By "bioactive ink" is meant a fluid or viscous substance for printing consisting of at least a pigment, a binder and a biocatalyst. In the present context, the term bioactive refers to the possibility of catalyzing redox reactions by incorporating a biocatalyst such as an enzyme.
[0028] According to a particular embodiment of the invention, the cathode ink formulation comprises:
[0029] (a) a double emulsion formulation, wherein the double emulsion formulation comprises a hydrogel bio-derived polymer as a first emulsion and a bio-derived hydrophobic wax as a second emulsion;
[0030] (b) and bioactive inks;
[0031] Herein, bioactive inks were added to double emulsion formulations.
[0032] In the cathode ink formulation of the present invention, the polymer of the hydrogel bio-derived polymer may be selected from the group consisting of chitosan, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, poly (acrylic acid).
[0033] According to the present invention, the bio-derived hydrophobic wax may be selected from the group consisting of beeswax, carnauba wax, candelilla wax, sunflower wax, berry wax, bayberry wax, lanolin, cetyl alcohol ester wax (cetyl palmitate) and other plant waxes.
[0034] The so-called "vegetable wax" refers to wax derived from plants.
[0035] According to the present invention, the bioactive ink may comprise mesoporous carbon, water, at least one polymer and a multi-copper enzyme. Preferably, the bioactive ink is added after the double emulsion is formed, because it contains enzymes and high molecular weight polymers (e.g., about 250 000 to 3000 000 Da) that are not fully compatible with the high shear rate process used to prepare the emulsion.
[0036] According to the present invention, the mesoporous carbon of the bioactive ink may be selected from the group consisting of carbon nanofibers, carbon black and carbon nanotubes.
[0037] According to the present invention, at least one polymer of the bioactive ink may be selected from the group consisting of chitosan, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, poly(acrylic acid).
[0038] According to the present invention, the multi-copper enzyme of the bioactive ink may be selected from the group consisting of bilirubin oxidase and laccase.
[0039] According to the present invention, the ratio of the second emulsion to the first emulsion of the double emulsion formulation may be 70 / 30 to 99 / 1, preferably 98 / 2.
[0040] According to the present invention, the bioactive ink may comprise 1% to 20%, preferably 15%, of the total weight of the formulation.
[0041] Another object of the present invention is also a hydrophobic biocathode comprising the cathode ink formulation of the present invention.
[0042] Another object of the invention is also a biofuel cell comprising the hydrophobic biocathode according to the invention.
[0043] Another object of the present invention is also a process for preparing the cathode ink formulation of the present invention, said process comprising the following steps:
[0044] a) preparing a first emulsion of a hydrogel bio-derived polymer;
[0045] b) preparing a second emulsion of a bio-derived hydrophobic wax;
[0046] c) mixing the first emulsion and the second emulsion to obtain a double emulsion formulation; and
[0047] d) mixing the double emulsion preparation obtained in step c) with a bioactive ink.
[0048] Another object of the invention is also the use of a hydrophobic biobinder in a biofuel cell, the hydrophobic biobinder comprising or consisting of a double emulsion formulation comprising as a first emulsion a hydrogel bio-derived polymer and as a second emulsion a bio-derived hydrophobic wax, as defined herein. The double emulsion makes the resulting layer sufficiently hydrophobic to increase the oxygen concentration near the catalytic centers, but allows sufficient hydration to maintain good proton conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1Represents polarization tests of 4 different cathode ink formulations. (squares) A - BW E4 95 / 5 (plus) B - BWE5 90 / 10 (cross) C - BW E6 98 / 2 (circles) D - PTFE.
[0050] Figure 2 Schematic representation of (A) a double emulsion formulation (hydrophobic biobinder) used in accordance with the present invention to provide (B) a hydrophobic biocathode comprising the double emulsion formulation and an added ink formulation (cathode ink formulation). (1) Water; (2) a hydrophobic bio-derived wax (second emulsion); (3) a hydrogel bio-derived polymer (first emulsion); (4) a water droplet; (5) a hydrophobic biocathode. DETAILED DESCRIPTION
[0051] Example 1: Biodegradable Hydrophobic Composition (Hydrophobic Biobinder) for Biofuel Cell Cathode
[0052] 1. Beeswax system preparation (double emulsion preparation)
[0053] Prepare a beeswax system formulation using the following materials:
[0054] -bleached beeswax (CAS: 8012-89-3)
[0055] -Chitosan from crab shells (cas: 9012-76-4) dispersed in water (3 wt%)
[0056] - Tween 20 (CAS: 9005-64-5) (same ratio as dry chitosan)
[0057] -Glycerol (CAS: 56-81-5) (0.25*dry weight of chitosan)
[0058] Four different beeswax emulsions were prepared with different ratios of wax / chitosan (weight: 0 / 100; 90 / 10; 95 / 5; 98 / 2).
[0059] For the preparation of the double emulsion formulation, beeswax was heated at 95°C until it was completely melted.
[0060] First Emulsion :
[0061] At the same time, chitosan, Tween 20 and glycerol dispersed in water were mixed and passed through a centrifuge at 25 000 rpm for 20 min. Rotor stator equipment.
[0062] Second emulsion :
[0063] This preparation (first emulsion) was then mixed with previously melted beeswax and passed through a sieve at 25,000 rpm for 30 minutes. Rotor stator equipment.
[0064] The double emulsion formulation renders the resulting layer sufficiently hydrophobic to increase the oxygen concentration near the catalytic center, but allows sufficient hydration to maintain good proton conductivity.
[0065] 2. Contact angle measurement of beeswax system preparations
[0066] The four double emulsion formulations were coated on glass at a controlled thickness of 200 μm and a doctor blade speed of 30 mm / s.
[0067] The samples were then heated in an oven at 40°C until the layers were completely dry.
[0068] Contact angles were determined using an Ossila contact goniometer and its associated software. An electronic pipette dispensed 10 μL drops of distilled water. Six samples were tested for each beeswax emulsion. Three contact angle measurements were performed for one sample and averaged between the left and right angles.
[0069] Beeswax / Chitosan Ratio Average contact angle (°) Chitosan 3 wt% 0 / 100 71(σ=9) BW 90 / 10 90(σ=4) BW E 95 / 5 98(σ=6) BW 98 / 2 100(σ=6)
[0070] As theory suggests, when the contact angle is between 0° and 90°, the system is hydrophilic. Conversely, when the contact angle is between 90° and 180°, it is hydrophobic.
[0071] The results show that the emulsion containing only chitosan is considered hydrophilic (average contact angle of 71°). On the other hand, the results show that all beeswax double emulsion formulations have a contact angle greater than or equal to 90°, which means that they can be considered hydrophobic.
[0072] Furthermore, the higher the percentage of beeswax in the double emulsion formulation compared to chitosan, the more hydrophobic the layer is. In fact, the double emulsion "BW E5" with a beeswax / chitosan ratio of 90 / 10 has an average contact angle of 90°, the double emulsion "BW E4" with a beeswax / chitosan ratio of 95 / 5 has an average contact angle of 98°, and the double emulsion "BWE6" with a beeswax / chitosan ratio of 98 / 2 has an average contact angle of 100°.
[0073] 3. Cathode ink preparation
[0074] Cathode ink formulations were prepared using three beeswax double emulsions, "BW E4", "BW E5" and "BW E6".
[0075] Briefly, to formulate the cathode ink formulations, the double emulsions were prepared as described above prior to final mixing.
[0076] The mesoporous carbon is also dispersed in advance using a rotor stator tool at high shear rate. This part generally requires at least 15 minutes of dispersion and is carried out at room temperature until every particle is dispersed.
[0077] The graphite particles, carbon dispersed in a polymer (chitosan), double emulsion beeswax and water were then mixed at low speed using a dispermat for 30 minutes. The enzyme (bilirubin oxidase) and its promoter (hemin) were then added to the cathode ink formulation and the system was stirred at room temperature for at least 1 hour.
[0078] Cathode formulations A, B, C and D consisted of mesoporous carbon (3 wt%), water, polymer (same proportions of each) and 1 wt% bilirubin oxidase. The only difference was the hydrophobic component (double emulsion component) which accounted for 15% of the overall ink formulation.
[0079] The cathode ink formulation is ready to be printed on a GDL (gas diffusion layer) substrate using a coating station.
[0080] The exact percentages are given in the table below.
[0081]
[0082] For comparison with a completely hydrophobic polymer, a reference using PTFE was also tested.
[0083] Example 2: Polarization Testing of Cathode Ink Formulations
[0084] Four different fuel cells are built by assembling the following layers:
[0085] - an outer layer made of glued cellulose paper having one opening dedicated to the cathode ventilation and two other openings for simultaneous contact with the anode and cathode;
[0086] - a printed cathode made of a cathode ink formulation (A; B; C; D) printed on a GDL; the GDL is on the side of the outer layer;
[0087] - A paper-based microfluidic layer;
[0088] -Use 1.5mg / cm 2 The reference anodic buckypaper functionalized with glucose oxidase, which is considered stable (functionalized side in contact with paper);
[0089] - GDL used as current collector for anode buckypaper;
[0090] - Another outer layer made of glued cellulose paper, which closes all the fuel cells (with two openings for contacting the cathode side and the anode side simultaneously).
[0091] The four different fuel cells were electrochemically tested. The electrolyte consisted of a buffer (sodium phosphate NaPB 0.1 M, pH 7), an electrolyte support (sodium sulfate Na 2 SO 4 These fuel cells were activated with a solution made of 0.1 M MgCl2 and 0.2 M glucose.
[0092] The experiment was repeated 5 times.
[0093] Polarization tests were performed using a potentiostat and its associated software EC-lab. The protocol was 30 seconds rest followed by a discharge current of -1μA / -5μA / -10μA…-500μA.
[0094] The results of polarization test ( Figure 1 ) show that formulations with a more important beeswax ratio have better results. This trend may be related to the contact angle results. In addition, after -150 μA, formulation C (BW E6 98 / 2) has a higher potential than formulation D (PTFE), indicating that an adjustable ratio between hydrophobic and hydrophilic properties works better than using only hydrophobic systems (such as using only PTFE). Therefore, the maximum efficiency threshold is a BW / CHIT ratio above 95 / 5. In addition, this result shows that a fully sustainable system has an advantage in use compared to molecules with very strong persistence (such as fluoropolymers).
[0095] References
[0096] 1.Atanassov et al.,ChemElectroChem.,1(11):1702-1704,2014
[0097] 2.Katz et MacVittie, Energy Environ. Sci., 6: 2791-2803, 2013
[0098] 3.Cosnier et al.,J.Power Sources,325:252-263,2016
[0099] 4. Sinha et al., J. Mater. Chem., 17: 3089-3103, 2007; DOI: 10.1039 / b703485g
[0100] 5.Park et al.,Applied Energy,87(7):2180-2186,2010 doi:10.1016 / j.apenergy.2009.11.021
[0101] 6.Qiu et al.,Int.J.Hydrogen Energy,38(14):5836-5844,2013
[0102] 7.Wei et al.,Int.J.Hydrogen Energy,40(7):3068-3074,2015
[0103] 8.Deshmukh et al.,https: / / doi.org / 10.1016 / j.jpowsour.2019.227284
[0104] 9.Roh et al.,Electrochem.Commun.,97:105-109,2018
[0105] 10.Oh et al.,Int.J.Hydrogen Energy,36(21):13695-13702,2011
[0106] 11.Li et al., Electrochem Commun.,11(4):897-900,2009
[0107] 12.Hiramitsu et al.,J.Power Sources,195(22):7559-7567,2010
[0108] 13.Chi et al.,Electrochim.Acta,277:110-115,2018
[0109] 14.Cazón et al.,Food Hydrocolloids,68:136-148,2017
[0110] 15.Jung et al.,J.Agric.Food Chem.,63(11):3031-3038,2015
[0111] 16.Wang et al.,J.Agric.Food Chem.,66(2):395-413,2018
[0112] 17.J.Agric.Food Chem.2004,52,6585-6591
[0113] 18.Hu et al.,LWT-Food Sci.Technol.,65:398-405,2016
[0114] 19.Wang et al.,2019J.Agric.Food Chem.2004,52,6585-6591
[0115] 20.Wu et al.,Food Hydrocolloids,30(1):82-91,2013
[0116] 21.Klangmuang et Sothornvit,2016DOI:10.1016 / J.LWT.2018.01.089
[0117] 22.Velickova et al.,LWT-Food Sci.Technol.,52(2):80-92,2013
[0118] 23.Neto et al.,J.Power Sources,324:208-214 2016
[0119] 24.Cooney et al.,Carbohydrate polymers 75(3):428-435,2009
[0120] 25.Reid,Thesis,2016
[0121] 26.Lohmann et al.,Environ.Sci.Technol.,54,12820-12828,2020。
Claims
1. A cathode ink formulation comprising a mixture of a hydrogel bio-derived polymer as a first emulsion and a bio-derived hydrophobic wax as a second emulsion and a bioactive ink comprising mesoporous carbon, water, at least one polymer and a multi-copper enzyme.
2. The cathode ink formulation of claim 1, wherein the cathode ink formulation comprises: (a) a double emulsion formulation, wherein the double emulsion formulation comprises a hydrogel bio-derived polymer as a first emulsion and a bio-derived hydrophobic wax as a second emulsion; (b) and bioactive inks; wherein the bioactive ink is added to the double emulsion formulation.
3. The cathode ink formulation according to claim 1 or 2, wherein the polymer of the hydrogel bio-derived polymer is selected from the group consisting of chitosan, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, poly (acrylic acid).
4. The cathode ink formulation according to any one of claims 1 to 3, wherein the bio-derived hydrophobic wax is selected from the group consisting of beeswax, carnauba wax, candelilla wax, sunflower wax, berry wax, bayberry fruit wax, lanolin, cetyl alcohol ester wax (cetyl palmitate) and other plant waxes.
5. The cathode ink formulation of claim 4, wherein the mesoporous carbon of the bioactive ink is selected from the group consisting of carbon nanofibers, carbon black, and carbon nanotubes.
6. The cathode ink formulation of claim 4, wherein the at least one polymer of the bioactive ink is selected from the group consisting of chitosan, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, poly (acrylic acid).
7. The cathode ink formulation of claim 4, wherein the multi-copper enzyme of the bioactive ink is selected from the group consisting of bilirubin oxidase and laccase.
8. The cathode ink formulation according to any one of claims 1 to 7, wherein the ratio of the second emulsion to the first emulsion of the double emulsion formulation is 70 / 30 to 99 / 1, preferably 98 / 2.
9. A cathode ink formulation according to any one of claims 1 to 8, wherein the bioactive ink comprises 1% to 20%, preferably 15%, of the total weight of the formulation.
10. A hydrophobic biocathode comprising the cathode ink formulation according to any one of claims 1 to 9.
11. A biofuel cell comprising the hydrophobic biocathode according to claim 10.
12. A method for preparing a cathode ink formulation according to any one of claims 1 to 9, comprising the steps of: e) preparing a first emulsion of a hydrogel bio-derived polymer; f) preparing a second emulsion of a bio-derived hydrophobic wax; g) mixing the first emulsion and the second emulsion to obtain a double emulsion formulation; and h) mixing the double emulsion formulation obtained in step c) with a bioactive ink comprising mesoporous carbon, water, at least one polymer and a multi-copper enzyme.
13. Use of a hydrophobic biobinder in a biofuel cell, the hydrophobic biobinder comprising a double emulsion, wherein the double emulsion formulation comprises a hydrogel bio-derived polymer as a first emulsion and a bio-derived hydrophobic wax as a second emulsion.